Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(a,\frac{1}{2\times3}+\frac{1}{3\times4}+\frac{1}{4\times5}+\frac{1}{5\times6}=\frac{1}{2}-\frac{1}{3}+\frac{1}{3}-\frac{1}{4}+\frac{1}{4}-\frac{1}{5}+\frac{1}{5}-\frac{1}{6}\)
\(=\frac{1}{2}-\frac{1}{6}=\frac{1}{3}\)
\(b,\left(1-\frac{1}{2}\right)\times\left(1-\frac{1}{3}\right)\times\left(1-\frac{1}{4}\right)=\frac{1}{2}\times\frac{2}{3}\times\frac{3}{4}\)
\(=\frac{1\times2\times3}{2\times3\times4}=\frac{1}{4}\)
\(a.60\times\left(\frac{7}{12}+\frac{4}{15}\right)\)
\(=60\times\left(\frac{35}{60}+\frac{16}{60}\right)\)
\(=60\times\frac{51}{60}\)
\(=51\)
\(b.\frac{1}{2}\times\frac{2}{3}\times\frac{3}{4}\times\frac{4}{5}\times\frac{5}{6}\times\frac{6}{7}\times\frac{7}{8}\times\frac{8}{9}\)
\(=\frac{1\times2\times3\times4\times5\times6\times7\times8}{2\times3\times4\times5\times6\times7\times8\times9}\)
\(=\frac{1}{9}\)
1) 1/5 . 5/4 + 1/5 . 5/4
= (1/5 + 1/5) . 5/4
= 1/5 . 5/4
= 1/4
2)tự làm
1.\(\frac{1}{5}\times\frac{5}{4}+\frac{1}{5}\times\frac{5}{4}\)
\(=\frac{1}{5}\times\frac{5}{4}\times2\)
\(=\frac{1\times5\times2}{5\times4}\)
\(=\frac{1}{2}\)
2.\(\frac{7}{6}\times\frac{2}{5}-\frac{1}{3}\times\frac{2}{5}+\frac{5}{6}\times\frac{2}{5}\)
\(=\frac{2}{5}\times\left(\frac{7}{6}-\frac{1}{3}+\frac{5}{6}\right)\)
\(=\frac{2}{5}\times\left(\frac{7}{6}-\frac{2}{6}+\frac{5}{6}\right)\)
\(=\frac{2}{5}\times\frac{5}{3}\)
\(=\frac{2}{3}\)
a; 60 \(\times\) (\(\dfrac{7}{12}\) + \(\dfrac{4}{15}\))
= 60 \(\times\) \(\dfrac{7}{12}\) + 60 \(\times\) \(\dfrac{4}{15}\)
= 35 + 16
= 51
a,\(60\times\left(\frac{7}{12}+\frac{4}{15}\right)\)\(=\frac{60\times7}{12}+\frac{60\times4}{15}\)
\(=\frac{12\times5\times7}{12}+\frac{15\times4\times4}{15}\)
\(=5\times7+4\times4\)
\(=35+16\)
\(=51\)
b, \(\frac{1}{2}\times\frac{2}{3}\times\frac{3}{4}\times...\times\frac{8}{9}\)\(=\frac{1\times2\times3\times4\times5\times6\times7\times8}{2\times3\times4\times5\times6\times7\times8\times9}\)
\(=\frac{1}{9}\)
a) 17 x 4 - 4 + 4 x 1
= 4 x ( 17 - 1 + 1 )
= 4 x 17
=428
b) 1 x 1 + 1 x 13 + 1
= 1 x ( 1 + 13 + 1 )
=1 x 15
=15
2 x 6 + 2 x 6 + 2
=2 x ( 6 + 6 + 1 ))
=2 x 13
=26
17 x 4 - 4 + 4 x 1
=17 x 4 + 4 x 1 - 4
=4 x (17+1) - 4
=4 x 18 - 4
=72 - 4 = 68
2 x 5 - 5 + 5 x 2
=2 x 5 + 5 x 2 - 5
=10+10-5=15
b, 1x1+1x13+1
= 1+13+1 = 15
2x6+2x6+2
=12+12+2=26
bạn có chép sai đề k z ???